Curcumin inhibits cancer progression through regulating expression of microRNAs - Siying Zhou; Sijie Zhang; Hongyu Shen; Wei Chen; Hanzi Xu; Xiu Chen; Dawei Sun; Shanliang Zhong; Jianhua Zhao; Jinhai Tang (Tumor Biology)
Curcumin, a major yellow pigment and spice in turmeric and curry, is a powerful anti-cancer agent. The anti-tumor activities of curcumin include inhibition of tumor proliferation, angiogenesis, invasion and metastasis, induction of tumor apoptosis, increase of chemotherapy sensitivity, and regulation of cell cycle and cancer stem cell, indicating that curcumin maybe a strong therapeutic potential through modulating various cancer progression. It has been reported that microRNAs as small noncoding RNA molecules are related to cancer progression, which can be regulated by curcumin. Dysregulated microRNAs play vital roles in tumor biology via regulating expressions of target genes and then influencing multiple cancer-related signaling pathways. In this review, we focused on the inhibition effect of curcumin on various cancer progression by regulating expression of multiple microRNAs. Curcumin-induced dysregulation of microRNAs may activate or inactivate a set of signaling pathways, such as Akt, Bcl-2, PTEN, p53, Notch, and Erbb signaling pathways. A better understanding of the relation between curcumin and microRNAs may provide a potential therapeutic target for various cancers.